2020
DOI: 10.36941/ajis-2020-0108
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Timing in Introducing Teacher Performance Evaluation on Effective Outcomes: The Case of One Education District in Zimbabwe

Abstract: This paper reports on a study that assessed how timing of introducing teacher performance evaluation in one district in Zimbabwe influenced the achievement of the desired outcomes.  The research was premised on the pragmatic research paradigm and underpinned by the Readiness Assessment, Design, Process, Significance (RADPS) conceptual framework. The convergent parallel mixed method design was employed for data gathering and analysis from randomly selected 292 teachers for the quantitative strand and 12 purposi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…But the emergence of the COVID-19 pandemic and subsequent global lockdowns prompted the unprecedented shift to exclusively virtual education for the first time in history (Assadi & Kashkosh, 2022;Haenilah et al, 2022;Musodza et al, 2020). In-service training, understood as the set of actions contributing to the professional development of teachers around the world, was no exception.…”
Section: Introductionmentioning
confidence: 99%
“…But the emergence of the COVID-19 pandemic and subsequent global lockdowns prompted the unprecedented shift to exclusively virtual education for the first time in history (Assadi & Kashkosh, 2022;Haenilah et al, 2022;Musodza et al, 2020). In-service training, understood as the set of actions contributing to the professional development of teachers around the world, was no exception.…”
Section: Introductionmentioning
confidence: 99%
“…Research by Ortiz-López et al (2022) found that teacher teaching competence affects teacher performance; Personal characteristics of a teacher have a significant influence on teacher performance (S. S. Wulandari et al, 2021). An inappropriate evaluation system for teachers causes low teacher performance (Musodza et al, 2020), therefore teachers are recommended to be able to do self-reflection in order to be able to improve their professional competence so that it has an impact on their performance (Martínez-Izaguirre et al, 2018).…”
Section: Introductionmentioning
confidence: 99%